Employing Two‐stage Derivatisation and GC–MS to Assay for Cathine and Related Stimulant Alkaloids across the Celastraceae. Issue 4 (26th January 2017) - Tembrock, Luke R.; Broeckling, Corey D.; Heuberger, Adam L.; Simmons, Mark P.; Stermitz, Frank R.; Uvarov, Jessica M.
Abstract: Introduction: Catha edulis (qat, khat, mirra) is a woody plant species that is grown and consumed in East Africa and Yemen for its stimulant alkaloids cathinone, cathine and norephedrine. Two Celastraceae species, in addition to qat, have been noted for their stimulant properties in ethnobotanical literature. Recent phylogenetic reconstructions place four genera in a clade sister to Catha edulis, and these genera are primary candidates to search for cathine and related alkaloids. Objective: Determine if cathine or related alkaloids are present in species of Celastraceae other than Catha edulis . Methods: Leaf samples from 43 Celastraceae species were extracted in water followed by basification of the aqueous extract and partitioning with methyl‐ t ‐butyl ether to provide an alkaloid‐enriched fraction. The extract was derivatised in a two‐stage process and analysed using GC–MS for the presence of cathine. Related alkaloids and other metabolites in this alkaloid‐enriched fraction were tentatively identified. Results: Cathinone, cathine and norephedrine were not detected in any of the 43 Celastraceae species assayed other than Catha edulis . However, the phenylalanine‐ or tyrosine‐derived alkaloid phenylethylamine was identified in five species. Nine species were found to be enriched for numerous sterol‐ and terpene‐like compounds. Conclusion: These results indicate that cathine is unique to Catha edulis, and not the compound responsible for the stimulant properties reported in related Celastraceae species. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A multi‐stage derivatisation process was used to examine alkaloid extractions from species across the Celastraceae to determine whether cathine or any similar compounds were present outside Catha edulis . Species for the study were selected based on a phylogenetic analysis and ethnobotanical accounts for stimulants in Celastraceae. Cathine was only detected in Catha edulis however the alkaloid phenylethylamine was found in four Celastraceae species but not Catha edulis .